Wearable flexible ultrasound microneedle patch for cancer immunotherapy - Haoyue Xue; Jing Jin; Xing Huang; Zhi Tan; Yushun Zeng; Gengxi Lu; Xin Hu; Keliang Chen; Yonglin Su; Xiaolin Hu; Xingchen Peng; Laiming Jiang; et al. (Nature Communications)
Abstract Clinical approaches for cancer therapy face several interrelated challenges involving inefficient drug delivery, potential adverse side effects, and inconvenience. Here, we present an integrated wearable flexible ultrasound microneedle patch (wf-UMP) that serves as a portable platform for convenient, efficient, and minimally invasive cancer therapy. The wf-UMP adopts an all-in-one bioelectronic concept, which integrates a stretchable lead-free ultrasound transducer array for acoustic emission, a bioadhesive hydrogel elastomer for robust adhesion and acoustic coupling, and a dissolvable microneedle patch loaded with biocompatible piezoelectric nanoparticles for painless drug delivery and reactive oxygen species generation. With soft mechanical properties and enhanced electromechanical performance, wf-UMP can be robustly worn on curved and dynamic tissue surfaces for easy and effective manipulation. In preclinical studies involving mice, wf-UMP demonstrated notable anticancer effects by inducing tumor cell apoptosis, amplifying oxidative stress, and modulating immune cell proliferation. Furthermore, the synergistic immunotherapy induced by wf-UMP and Anti-PD1 further improved anticancer immunity by activating immunogenic cell death and regulating macrophages polarization, inhibiting distant tumor growth and tumor recurrence.